Does sponsorship of electrophysiology and devices presentations alter conflict of interest disclosures?. (24th May 2021) - Camm, CJF; Crawford, W; Bello, A; Raouf, Z; Schaefer, A; Prachee, I; Olivarius-Mcallister, J; Ginks, M; Nicol, E
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Interaction with industry is often required for the development of electrophysiology (EP) and devices research. Findings from industry-funded research are often presented at sponsored sessions during international conferences. However, industry interactions produce potential conflict of interests (COIs). Such COIs must be disclosed appropriately when presenting research findings to allow viewers to interpret the results correctly. This is particularly true during sponsored sessions. Purpose: To assess whether session sponsorship affects the presentation of potential COIs in EP and devices presentations. Methods: Recorded presentations from the Arrhythmia & Devices section of ESC Annual Congresses 2016-2020 were assessed. Presentations were excluded if the original presentation contained no slides, was a panel discussion, it was a non-scientific presentation, or part of the presentation was missing. Sponsorship information was gathered from presentation meta-data. Chi-squared and Mann-Whitney U tests were used to assess differences between groups for dichotomous and continuous data respectively. Results: Of 1, 153 presentations assessed, 1, 017 were suitable for inclusion. Of these 14% (n = 142) were sponsored sessions. COI disclosure slides were more likely to be missing in sponsored sessions (13.4%, n = 19) compared with non-sponsored sessions (6.2%, n = 54), p = 0.002. In those with COI disclosure slides, sponsored presentations contained a greater median number of COIs (12, IQR 6-19) compared with non-sponsored sessions (1, IQR 0-5), p < 0.0001. Conversely, the time-per-word spent on COI disclosures was approximately 50% lower in sponsored sessions (125ms, IQR 76-217ms) compared with non-sponsored sessions (250ms, IQR 125-375ms), p < 0.0001. Furthermore, presenters at sponsored sessions were much less likely than those at non-sponsored sessions to provide sufficient verbal details of their conflicts (0% vs 8.5% respectively, p = 0.0008). These findings were not materially altered when limited to only those presentations with COIs. Conclusions: Sponsored sessions make up about one seventh of all EP/devices presentations at the ESC annual congress. Presenters at sponsored sessions were less likely to present a COI disclosure slide. Sponsored presentations had a higher number or of potential COIs, yet they were displayed for a far shorter time. This suggests that sponsored sessions have a higher risk of potential bias which viewers are not provided sufficient opportunity to assess.